THE IMPACT OF KOREAN CULTURE ON UZBEK PEOPLE - Nag'matullayeva Ra'no; Maftuna Nurova (TADQIQOTLAR, 2025)
Annotation In today’s world, motivating people and laborers in their individual and proficient lives is pivotal. This paper investigates how Korean culture, particularly by means of media, dialect, and way of life impacts, rouses youthful Uzb